Pengaruh Lingkungan, Sikap, Dan Akademik Terhadap Niat Berwirausaha Siswa SMK - Jaya Bangsa (Jurnal Ekonomi, Manajemen dan Akuntansi (JEMA) Universitas Ngudi Waluyo, 2020)
The importance of entrepreneurship in a country can increase per capita income in A country, beside that the number of unemployment also decrease. A country can be said to reach prosperity level if the number of entrepreneurship on a country is 2% of the whole population of the country. Vocational school is widely getting favor more by society, because the vocational school graduate is claiming easier to get a job when graduate from school, entrepreneurship lesson which serve by vocational school have a purpose to create new entrepreneur after graduate from school . This researched involving 200 respondents from the student of SMK Telekomunikasi Tunas Harapan this research is analyz using multiples regrating analysis with SSPS 16 . The research result show that the 3 variable which are environment, attitude, and academics. Influence motivation the student of SMK Telekomunikasi Tunas Harapan to entrepreneurships . But the most influence variable is academics , then follow by attitude and environment